"We can't do anything": The experiences of students with visual impairments in physical education classes in Brazil. (May 2018) - Tanure Alves, Maria Luíza; Haegele, Justin A; Duarte, Edison
Inclusion is a subjective experience related to sense of belonging and acceptance. In this way, the specific nature of a disability can have particular implications on the obstacles one experiences in physical education. Thus, the main objective of this study was to investigate the experiences of students with visual impairments in physical education classes in Brazil from an individual and subjective perspective. Eight students with visual impairments (five female students and three male students) between 13 and 18 years participated in the study. Interviews, which utilized a semi-structured interview guide, were used to obtain important information from the students. Interview transcripts were analyzed by the content analysis technique. Results revealed two main themes: (1) participation and (2) social interaction. Exclusion from physical education activities was omnipresent among the experiences of students with visual impairments. Physical education teachers did not recognize physical education classes as a place for student with visual impairments.